\[
A = P_{\hat{x}}^2\ v_{\hat{y}} - P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{x}} - R^2\ v_{\hat{y}} \\
B = P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{y}} - P_{\hat{y}}^2\ v_{\hat{x}} + R^2\ v_{\hat{x}} \\
\]
\( A^2 + B^2 = 0 \) は \( A = 0,\ B = 0 \) の場合。
\[
P_{\hat{x}}^2\ v_{\hat{y}} - P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{x}} - R^2\ v_{\hat{y}} = 0\\
P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{y}} - P_{\hat{y}}^2\ v_{\hat{x}} + R^2\ v_{\hat{x}} = 0 \\
\]
\[
P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{x}} + ( R^2 - P_{\hat{x}}^2 )\ v_{\hat{y}} = 0\\
( R^2 - P_{\hat{y}}^2 )\ v_{\hat{x}} + P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{y}} = 0 \\
\]
\[
P_{\hat{x}}\ P_{\hat{y}}\ P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{x}} + P_{\hat{x}}\ P_{\hat{y}}\ ( R^2 - P_{\hat{x}}^2 )\ v_{\hat{y}} = 0\\
( R^2 - P_{\hat{x}}^2 )\ ( R^2 - P_{\hat{y}}^2 )\ v_{\hat{x}} + ( R^2 - P_{\hat{x}}^2 )\ P_{\hat{x}}\ P_{\hat{y}}\ v_{\hat{y}} = 0 \\
\]
\[
( R^2 - P_{\hat{x}}^2 )\ ( R^2 - P_{\hat{y}}^2 )\ v_{\hat{x}}
- P_{\hat{x}}^2\ P_{\hat{y}}^2\ v_{\hat{x}} = 0 \\
\]
\[
( R^4 - R^2 ( P_{\hat{x}}^2 + P_{\hat{y}}^2 ) )\ v_{\hat{x}} = 0 \\
\ \\
R^2\ ( R^2 - ( P_{\hat{x}}^2 + P_{\hat{y}}^2 ) )\ v_{\hat{x}} = 0 \\
\ \\
R^2\ P_{\hat{z}}^2\ v_{\hat{x}} = 0 \\
\ \\
v_{\hat{x}} = 0 \\
\]
\( v_{\hat{x}} = 0 \) となるのは,\( P = Q \) の場合であり,即ち \( P_z = 0 \) の場合である。
そしていまは,\( P_z \ne 0 \) が条件になっている。
|